ANALISIS LINGUISTIK PRINSIP KERJA SAMA DALAM TUTURAN CERITA HUMOR NAWADIR JUHA LI AL-ATHFAL - Ulam, Asyifa; Emzir, Emzir; Nuruddin, Nuruddin (Arabi : Journal of Arabic Studies, 2018)
The purpose of this study was to describe (1) the compliances and deviations of the principle of cooperation in the speech of Arabian humorous story "Nawadir Juha Li Al-Athfal”, (2) the speech context in the story. This research used descriptive methods with qualitative approach. The focus of this study was the speech of compliances and deviations of cooperation principle which was used in Arabian humorous story by using methods and techniques to collect the data. In the provision of data, note and record technique was used, namely selecting the text and recording data that contained speech of compliance and deviation toward the principles of cooperation. The result of this research showed the speech of Arabian humorous story "Nawadir Juha Li Al-Athfal” contained elements of compliance and deviation toward the principles of cooperation with all of four maxims: maxim of quantity, maxim of quality, maxim of relevance, and maxim of manner.